2016
DOI: 10.1017/s0007114516001781
|View full text |Cite
|
Sign up to set email alerts
|

Skeletal effect of casein and whey protein intake during catch-up growth in young male Sprague–Dawley rats

Abstract: The aim of the present study was to determine whether the type of protein ingested influences the efficiency of catch-up (CU) growth and bone quality in fast-growing male rats. Young male Sprague-Dawley rats were either fed ad libitum (controls) or subjected to 36 d of 40 % food restriction followed by 24 or 40 d of re-feeding with either standard rat chow or iso-energetic, iso-protein diets containing milk proteins -casein or whey. In terms of body weight, CU growth was incomplete in all study groups. Despite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
29
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(35 citation statements)
references
References 35 publications
6
29
0
Order By: Relevance
“…In our previously described study in RES rats refed with casein- or whey-based diets [43], we found that re-feeding with whey led in the long term to linear growth and bone health similar to that achieved by re-feeding with casein, but with a lesser weight gain. These results suggest that a whey-based diet may circumvent long-term obesogenic complications of catch-up (CU) growth.…”
Section: The Influence Of Milk and Its Proteins On Weight And Body Cosupporting
confidence: 57%
See 2 more Smart Citations
“…In our previously described study in RES rats refed with casein- or whey-based diets [43], we found that re-feeding with whey led in the long term to linear growth and bone health similar to that achieved by re-feeding with casein, but with a lesser weight gain. These results suggest that a whey-based diet may circumvent long-term obesogenic complications of catch-up (CU) growth.…”
Section: The Influence Of Milk and Its Proteins On Weight And Body Cosupporting
confidence: 57%
“…To study the effect of casein and whey on bone structure and quality we used a rat model of nutrition-induced CU growth in which animals were allowed to eat 1 of 3 isocaloric, isoprotein diets differing in the origin of the protein, whether vegetable, casein, or whey [43]. Animals were analyzed after 24 or 40 days of re-feeding.…”
Section: The Influence Of Milk and Its Proteins On Bone Healthmentioning
confidence: 99%
See 1 more Smart Citation
“…Using microcomputed tomography analysis for the evaluation of bone morphology and micro-architecture ex vivo [7], we (G.G.-Y.) and others have shown that nutrition affects GP height as well as bone modeling of young bones and that the quality of the bone is affected by nutritional manipulation [7-9]. Fasting and food restriction impair the rate of longitudinal bone growth and reduce the height of the GP, the number of proliferative and hypertrophic chondrocytes per column, and the height of terminal hypertrophic chondrocytes [10, 11].…”
Section: Introductionmentioning
confidence: 99%
“…It is generally accepted that milk intake contributes to the bone remodeling process because of its physiological role in promoting skeletal growth in newborn animals. In addition to their high nutritional value, milk proteins such as casein and whey protein significantly affect bone health (2)(3)(4)(5). We previously demonstrated in both in vitro and in vivo studies that milk whey protein promotes bone formation and inhibits bone resorption (6)(7)(8)(9).…”
mentioning
confidence: 99%